Morphological and molecular characterization of Trichoderma species isolated from rhizosphere soils in Malaysia - Syd Abdul Rahman, Sharifah Siti Maryam; Mohd Zainudin, Nur Ain Izzati; Aris, Asma; Abd Aziz, Nor Azwady (Malaysian Society for Microbiology, 2021)
Aims: Knowledge of the Trichoderma taxa is important for both control efficiency and environmental conservation. Therefore, the objective of this study is to isolate and identify Trichoderma species from various rhizosphere soil samples using phenotypic and molecular characterization. Methodology and results: Native Trichoderma spp. were isolated from agricultural fields in 17 sites from seven states of Malaysia. These isolates were characterized via morphological observation and molecular phylogenetic analysis based on the translation elongation factor-1α (tef1-α) gene. About 42 isolates were classified into eight Trichoderma species, which are Trichoderma asperellum, T. hamatum, T. harzianum, T. koningiopsis, T. rodmanii, T. spirale, T. viride and T. virens. Comparison of DNA sequences of tef1-α showed that the isolates were 98-100% similar to respective Trichoderma species from GenBank, thus confirming the fungal identity. Phylogenetic trees of maximum likelihood (ML) dataset of tef1-α inferred that the isolates were clustered according to species. Conclusion, significance and impact of study: Findings in the present study will be beneficial for the purposes of biodiversity conservation and plant disease management using biocontrol agents.